Safety management in a competitive business environment - Sinay. J. (Jurai) (Ergonomics design and management, 2014)
The book provides information necessary for systematic management of traditional as well as emerging risks in the man-machine-environment system, especially in industrial technologies. It is intended for managerial staff of various levels of management as well as product distribution workers, and for education of professionals in the fields of occupational safety and health (OSH), safety of technological systems and partially also civil security" -- Provided by Publisher